Deep groundwater irrigation altered microbial community and increased anammox and methane oxidation in paddy wetlands of Sanjiang Plain, China - Li, Huai; Song, Aiwen; Qiu, Ling; Liang, Shen; Chi, Zifang (Frontiers in Microbiology, 2024)
had crucial effects on microbial community under phylum-and genus-levels.Microorganisms under shallow groundwater irrigation were highly sensitive to environmental changes, and Fe-anammox, nitrification, and methane oxidation were favorable under deep groundwater irrigation. This study highlights the importance of comprehensively revealing the microbial community and function of paddy wetlands under groundwater's irrigation and reveals the underlying function of indigenous microorganisms in agricultural non-point pollution control and greenhouse gas abatement.